Extensive Epidural Steatitis and Epaxial Myositis Associated with Intramuscular Injection of Melarsomine Dihydrochloride in Two Dogs - Arnold, Susan A.; Kent, Marc; Ruby, Jennifer L.; Clarke, Lorelei L.; Barber, Renee M.; Platt, Simon R. (VCOT Open, 2020)
This is a retrospective case series in which clinicopathological and imaging findings associated with neurological complications secondary to melarsomine dihydrochloride administration are reported in two dogs with Dirofilaria immitis infection. Following intramuscular injection of melarsomine dihydrochloride based on manufacturers' guidelines, two dogs developed acute, progressive, nonambulatory paraparesis or paraplegia. Magnetic resonance imaging was suggestive of epidural steatitis, resulting in compression of the spinal cord and spinal cord oedema. In one dog, emphysematous myositis throughout the lumbar paravertebral muscles was present. Hemilaminectomy with the intent of achieving spinal cord decompression and obtaining specimens for microbiological and histopathological evaluation was performed in both dogs. One dog partially regained function postoperatively whereas the other was euthanatized intraoperatively. Histologically, epidural steatitis was observed in the surviving dog and epidural steatitis, myonecrosis and grey and white matter changes in the spinal cord were observed in the euthanatized dog. Microbiological testing failed to identify bacteria from the affected tissues. Both cases highlight the potential for the development of extensive epidural steatitis and consequent spinal cord compression following intramuscular administration of melarsomine dihydrochloride. Further investigation into the optimal therapeutic intervention in dogs experiencing neurological complications following melarsomine administration is warranted.
Keywords: melarsomine dihydrochloride; epidural steatitis; myelopathy; MRI; dog